2022
DOI: 10.3390/nu14153231
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with NAD+ and Its Precursors to Prevent Cognitive Decline across Disease Contexts

Abstract: The preservation of cognitive ability by increasing nicotinamide adenine dinucleotide (NAD+) levels through supplementation with NAD+ precursors has been identified as a promising treatment strategy for a number of conditions; principally, age-related cognitive decline (including Alzheimer’s disease and vascular dementia), but also diabetes, stroke, and traumatic brain injury. Candidate factors have included NAD+ itself, its reduced form NADH, nicotinamide (NAM), nicotinamide mononucleotide (NMN), nicotinamide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Hence, it may be conceivable to use the extracellular NAD present at the target site of some tumors for activation of the enzyme for delivery of a potent CPP-drug, thereby adding an additional level of safety to avoid off-target effects. On another note, since it has been often described that NAD levels decline with age, supplementation with NAD and its precursors is a currently debated topic to counteract age-related diseases such as Alzheimer’s, but also diabetes, , which may be a considerable option to boost NAD levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it may be conceivable to use the extracellular NAD present at the target site of some tumors for activation of the enzyme for delivery of a potent CPP-drug, thereby adding an additional level of safety to avoid off-target effects. On another note, since it has been often described that NAD levels decline with age, supplementation with NAD and its precursors is a currently debated topic to counteract age-related diseases such as Alzheimer’s, but also diabetes, , which may be a considerable option to boost NAD levels.…”
Section: Discussionmentioning
confidence: 99%
“…39 Hence, it may be conceivable to use the extracellular NAD present at the target site of some tumors for activation of the enzyme for delivery of a potent CPP-drug, thereby adding an additional level of safety to avoid off-target effects. On another note, since it has been often described that NAD levels decline with age, supplementation with NAD and its precursors is a currently debated topic to counteract age-related diseases such as Alzheimer's, but also diabetes, 40,41 which may be a considerable option to boost NAD levels. For cryptophycin directly conjugated to L17E we observed potency in the nanomolar range, comparable to free cryptophycin in the modified toxicity assay where the compounds were washed from the cells after 2 h of incubation, rather than left on the cells for 72 h. This explains the difference from the low three-digit picomolar toxicity value expected of solitary cryptophycin.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Still, it emphasized the need for controlled clinical research to determine the efficacy of NAD (+) precursor supplementation in addressing cognitive health in humans. [ 12 ]…”
Section: Lifestyle-based Interventionsmentioning
confidence: 99%
“…Elevated NAD + in the brain can help improve cognitive dysfunction [ 39 ]. In a 2021 study of NMN to improve CICI-induced cognitive dysfunction, it was found that feeding C57 mice at a dose of 250 mg/kg body weight increased their NAD + levels in the hippocampus [ 40 ].…”
Section: Oral Nmn and Exercise Enhance Nad + In Vivomentioning
confidence: 99%